ANALYSIS OF MICROBIOLOGY QUALITY OF SURGICAL ROOM AIR BASED ON HOSPITAL TYPE AND ITS IMPACT ON THE ENVIRONMENT AND HEALTH IN EAST JAVA ON 2019 - Rositasari, Dianori (International Journal of Psychosocial Rehabilitation, 2020)
Hospitals as a means of health care, as well as a gathering place for sick and healthy people so that it has the potential to become a place of disease transmission and enables environmental pollution and health problems. One problem that often occurs is nosocomial infection. In Indonesia, nosocomial infections are quite high at 6-16% with an average of 9.8%. Environmental factor that influence nosocomial infections is air microbiology quality . Toanalyze microbiological quality of air in surgical room by hospital type and its impact on the environment and health in East Java on 2019.: This type of research was quantitative with cross sectional design, using secondary data from the laboratory testCenter for Environmental Health Engineering and Disease Control Surabaya which consisting of hospital surgical room air germs number data in East Java on 2019. Data were processed using statistical techniques, analyzed descriptively andwith cross tabulation (crosstab). Air germs number in surgical room both high and low can be found in all types of hospitals were Type A, B, C, and D. However, the highest germs number was found in type B hospitals. The highest surgicalroom air germ number was 1885 CFU/m3 . The highest average surgical room air germs number (144 CFU/m3 ) was found in the type A hospital group. The maximum limit of surgical room air germs is based on Regulation of Health Minister Number 7 Year 2019 which is 35 CFU/m3. There was a weak correlation between the surgical room air germs numberand type of hospital (coefficient contingency = 0.287). Microbiological quality of air in hospital surgical room in East Java with the air germs number, which wasnot qualify exceed 50%,are hospitals with types A, C, and D. Disciplined monitoring and supervision is needed, because the Surgical room is a very high risk zone so the airborne germs count needs to be controlled properly so it does not exceed quality standards.